Antifungal prophylaxis in newly diagnosed AML patients–Adherence to guidelines and feasibility in a real life setting. Issue 9 (15th May 2017) - Berking, Sophie; Doedens, Daphne; Horns, Heidi; Fiegl, Michael; Ostermann, Helmut; Rieger, Christina T.
Summary: Antifungal posaconazole prophylaxis for AML patients receiving induction chemotherapy has been routine at our centre since 2009. This retrospective study examined the feasibility and practicability of our prophylaxis guidelines in clinical practice. Data sets of 90 patients undergoing induction‐chemotherapy for AML between 2011 and 2014 were evaluated regarding adherence to local guidelines for the administration of antifungal prophylaxis with posaconazole. 75.5% of the 90 patients received posaconazole prophylaxis. All but eight patients received the recommended dosage. A total of 77.95% on prophylaxis had serum galactomannan measured twice weekly. Contradicting our guidelines, 89.70% of patients received concomitant therapy with PPI. Overall, 16.17% of patients had prophylaxis discontinued and started empirical antifungal treatment in the absence of diagnostic criteria for IFI. The breakthrough IFI rate was 36.76% (proven, probable and possible) with 7.35% of infections being classified as proven or probable. Although limited by a small sample size, our study demonstrates the feasibility of local guidelines in a real life setting and outlines areas for improvement in both guidelines and clinical practice. We also highlight the importance of ensuring awareness of guidelines and raise questions about a uniform approach to antifungal prophylaxis in AML patients.